Photography and painting: mutual relation in the distancing from mimesis (Palíndromo, 2015)
Through a brief critical historical study, this article aims to show the trans- formation of occidental thought  about the mimetic character of representation in painting and how photography per- formed an important role in this change, when it transferred for her the compro- mise with the copy of reality. The investi- gation considers the concept of mimesis pondered by Plato and Aristotle about the art, which had as one of its consequen- ces the appreciation for similarity to re- ality in an artistic work, reflection which permeated the occidental esthetics for a long time. By showing initial attempts to unlink pictorial and photographic pro- duction from the imposition of seeking the verisimilitude, modernist movements reveal trends and attempts to replace the problem of representation.
Keywords: mimesis; photography; painting; representation